2007
DOI: 10.1111/j.1537-2995.2007.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Weak D phenotypes and transfusion safety: where do we stand in daily practice?

Abstract: Serology is very sensitive to detect weak D Types 1, 2, and 3, but there is no cutoff to distinguish variants of clinical significance. When molecular analysis is not available, it is proposed that a D+ status for blood recipients found to be weak D with a sensitive method be assigned, except for women of childbearing age or younger, because of the remaining possibility to be partial D or other rare weak D who can be immunized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
0
26
0
3
Order By: Relevance
“…This can lead to errors in D typing in both patients and donors. The use of different technologies for blood typing can complicate this problem 13‐19 . In this report, we studied the similarities between the reactivity of different anti‐D MoAbs and the weak D phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to errors in D typing in both patients and donors. The use of different technologies for blood typing can complicate this problem 13‐19 . In this report, we studied the similarities between the reactivity of different anti‐D MoAbs and the weak D phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, differences in the various antibodies' reactivity must be considered in relationship with the technologies used for blood typing 13‐17 . Difficulties in D typing could be overcome by the routine use of molecular biology.…”
mentioning
confidence: 99%
“…If, however, only serological testing is being used, this policy is difficult to apply because identification of variants is often not possible. Noizat‐Pirenne et al () observed a range of reactivity for weak D of the same type, tested with the same reagent by a gel matrix technique.…”
Section: Testing In Patients and In Pregnancymentioning
confidence: 97%
“…In two samples with D+C‐c+E+e+ phenotype, a suppressed expression of the e antigen on RBCs was noted. This altered expression was identified before when associated with C X [19, 24] but also with Cys16 and VS [3, 19]. In the other samples with the e‐specific nucleotides in homozygous occurrence, a depressed expression of e S was not detected, explainable by masking of the aberrant haplotype by the conventional Rhe encoded on the partner chromosome.…”
Section: Discussionmentioning
confidence: 76%